High-Density Lipoproteins and Coronary Artery Disease: A Single-Center Cohort Study. (September 2014) - Schaffer, Alon; Verdoia, Monica; Barbieri, Lucia; Aprami, Toni Mustahsani; Suryapranata, Harry; Marino, Paolo; Luca, Giuseppe De
Our goal was to estimate the role of high-density lipoprotein cholesterol (HDL-C) in predicting the prevalence and extent of coronary artery disease (CAD) in 3280 patients undergoing coronary angiography. Predictors of lower HDL levels (<32 mg/dL) were male gender ( P < .001), diabetes mellitus ( P = .03), renal failure ( P = .01), higher low-density lipoprotein and total cholesterol ( P < .001, respectively), triglycerides ( P < .001), and white blood cells ( P < .001), aging ( P < .001), previous myocardial infarction ( P = .02) and hemoglobin ( P < .001), treatment with angiotensin-receptor blockers ( P < .001), and statins ( P = .002). The HDL-C levels were significantly inversely associated with prevalence of CAD ( P < .001, adjusted odds ratio [OR] [95% confidence interval, CI] = 1.35 [1.25-1.45], P < .001), and HDL-C <44 mg/dL was best the predictive value of the risk of CAD, (adjusted OR [95%CI] = 1.61 [1.24-2.1], P < .001). We found significant association between HDL-C and the risk of CAD; a value <44 mg/dL was the best cutoff in the prediction of CAD.